Design of an Interactive System MuseumUser Oriented - Mihura López, Rocío; Barneche Naya, Viviana; Hernández Ibáñez, Luis Antonio (Estudios sobre el Mensaje Periodístico, 2013)
This paper proposes the application of existing knowledge about the museum visitor to the design of interactive systems that are common today in the museum, in order to improve the educational experience of this peculiar user.